(untitled) (Journal of the Bangladesh Agricultural University, 2010)
An experiment was carried out in a roadside agroforestry system established along farm roadsides of Bangladesh Agricultural University, Mymensingh, to investigate the effects of pruning and pollarding on shoot development in Sesbania grandiflora L. Six treatment combinations with the stock plants studied during the period from August to September, 2007. The results revealed that the different pruning and pollarding levels had significant variations on the parameters studied at different days after pruning (DAP). Among the treatments the pollarded shoot tip with lower and upper branch pruning produced the highest number of new branches (572) followed by the treatment of intact shoot tip with lower and upper branch pruning with 454 new branches at 60 DAP. The new branches produced from pruning and pollarding treatments attained its maximum length within a very short time. Maximum branch length (24.66 cm) was observed in the treatments of pollarded shoot tip with lower and upper branch pruned off condition followed by the treatment of intact shoot tip with lower and upper branch pruned off condition which attained 17.67 cm of length at 21 DAP. Again the pollarded shoot tip with lower and upper branch pruning produced 1127 number of leaves followed by the treatment of intact shoot tip with lower and upper branch pruning produced 999 leaves at 60 DAP. The results of this study suggest that the severely pruned plant (both lower and upper branch pruned along with pollarded shoot tip) not only produced huge amount of shoot biomasses but also enhance the development of new shoots within a very short period. Keywords: Sesbania grandiflora L.; Agroforestry; Pruning; Pollarding. DOI: 10.3329/jbau.v6i2.4823 J. Bangladesh Agril. Univ. 6(2): 285-289, 2008